The prognostic significance of cardiac sympathetic activity and dyssynchrony in cardiac resynchronization therapy in ischemic and non-ischemic heart failure patients. (8th February 2021) - Mishkina, A; Zavadovsky, K; Saushkin, V; Lebedev, D; Lishmanov, Y
Abstract: Funding Acknowledgements: Type of funding sources: Foundation. Main funding source(s): Russian Foundation for Basic Research Introduction: Impaired cardiac sympathetic activity and contractility are associated with poor prognosis in patients with heart failure after cardiac resynchronization therapy (CRT). There are few prognostic data of the cardiac sympathetic activity and dyssynchrony in patients with chronic heart failure of various etiologies. Purpose: To examine the prognostic significance of scintigraphic cardiac sympathetic activity and contractility in predicting the response to CRT and to assess the differences between patients with ischemic (IHF) and non-ischemic (NIHF) heart failure. Methods: This study included 38 heart failure patients (24 male; mean age of 56 ± 11 years; 16 patients with ischemic etiology), who were submitted to CRT. Before CRT all patients underwent 123I-metaiodobenzylguanidine (123I-MIBG) imaging for cardiac sympathetic activity evaluating: early and delay heart to mediastinum ratio (eH/M and dH/M), summed MIBG Score (eSMS and dSMS). Moreover all patients underwent gated SPECT with the assessments of left ventricle dyssynchrony indexes: standard deviation (SD) and histogram bandwidth (HBW). In addition, all patients underwent gated blood-pool SPECT (GBPS) to assessed ejection fraction (EF) and stroke volume (SV) of both ventricles. Results: One year after CRT response defined as LV ESV decreased by≥15% and/or LV EF increase by≥5%. Baseline cardiac sympathetic activity parameters showed significant differences between responders and non-responders only in NIHF patients: eH/M: 2.27 (2.02–2.41) vs. 1.64 (1.32–2.16); dH/M: 2.18 (2.11–2.19) vs. 1.45 (1.23 – 1.61); eSMS: 7 (5-7) vs. 15.5 (10–28.5); dSMS: 10 (10–13) vs. 16.5 (15.5–29). Significant differences in baseline LV dyssynchrony indexes between responders and non-responders were in patients of both group: in NIHF patients - SD: 54.3 (43–58) degree vs. 65 (62–66) degree; HBW: 179.5 (140–198) degree vs. 211 (208-213) degree, p < 0.054 in IHF patients - HBW: 162 (115.2–180) degree vs. 115.2 (79.2–136.8) degree. Contractility of RV was significantly differed between responders and non-responders in IHF patients: RV EF: 54.5 (41-56) % vs. 44.5 (37–49.5) %; RV SV: 80 (69-101) ml vs. 55.5 (50–72.5) ml. According to univariate logistic regression analyses in IHF patients LV dyssynchrony indexes – SD (OR = 1.55; 95% CI 1.09-2.2; p < 0.5) and HBW (OR = 1.13; 95% CI 1.02-1.24; p < 0.5), as well as RV indexes – RV EF (OR = 1.11; 95% CI 1.001-1.23; p < 0.5), RV SV (OR = 1.07; 95% CI 1.003-1.138; p < 0.5) were predictors of CRT response. In the group of NIHF patients, dH/M (OR = 1.47; 95% CI 1.08-2; p < 0.5), SD (OR = 0.83; 95% CI 0.73-0.95; p < 0.5), HBW (OR = 0.96; 95% CI 0.93-0.99; p < 0.5) showed the predictive value in terms of CRT response. Conclusion: Scintigraphic methods can be used to select patients for CRT. Cardiac 123I-MIBG scintigraphy and gated SPECT may be used for predicting CRT response in NIHF patients. Whereas in IHF patients ECG-gated SPECT and GBPS may be valuable for predicting the response to CRT.